Bioethical aspects of the management of patients with Acquired immunodeficiency syndrome - Maria de Jesús Sánchez Bouza; Pedro Sánchez Frenes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Bioethical aspects related with the prevention, diagnosis and treatment of patients with AIDS are present in the Cuban strategy to fight the epidemic. Through the revision of the essentials and principles of Bioethics, we analyze the problems that doctors face when treating these patients and aspects related with education for health in the case of this disease. It also outlines the association between these principles and the disposition, manifested or not, of theses patients to be part of some researches. This infection should be the target of permanent analysis by the Bioethics due to the constant challenges that it represent for medical staff and for society, either for the prevention, treatment and care, or for other kids of actions. Cuba has exceptional results in this field.